FROM MASS TO COMMUNITY: SMALL GROUP STRATEGY AS MITIGATION FOR SPIRITUAL ALIENATION IN THE DIGITAL AGE - Evans Winata (Jurnal Penelitian Progresif, 2026)
The digital era presents a paradox: unprecedented connectivity coexists with profound spiritual alienation. Contemporary churches, particularly those exceeding 200 members, increasingly experience "crowds without community"—high attendance coupled with shallow relational engagement. This qualitative study analyzes the limitations of mass-oriented ministry models and proposes small group structures as strategic solutions. Drawing from theological foundations (Acts 2:42-47; 1 Corinthians 12:12-27), sociological theory (Dunbar's Number), and empirical research, this paper demonstrates that churches prioritizing secondary orientations (buildings, finances) over primary missions (spiritual formation, discipleship) risk organizational dysfunction and spiritual superficiality. Small groups (8-12 members) provide intensive spiritual formation through authentic fellowship and organic integrity monitoring through relational accountability, while addressing contemporary challenges including digital literacy deficits and civic responsibility formation. The study concludes with a paradigm shift from organizational mass structures to organic relational networks.